Belgium Wrestles with its Identity(ies) - Vincent Dujardin (Ksiegarnia Akademicka Publishing, 2021)
In this paper the author reconsiders the approach taken by Belgian politicians, working to promote European integration, vis-à-vis the question of European identity, roots and values, as well as their attitude towards European political objectives. We compare these views with those of French authors or politicians. Finally, we examine the current issues surrounding Belgian identity, caught betweenthe French-speaking community and the increasingly strong Flemish identity. By way of a conclusion, I shall try to show how Belgium, with its identity-related issues, is sometimes presented as a ‘test lab for Europe’, as it was in the past, in completely different contexts, in 1921 at the time of the BLEU (Belgo-Luxembourg Economic Union) and in 1944 with the founding of the Benelux union.